The Influence Of Price And Service Quality On Purchasing Decisions For Cafe Goela Gelato In Pontianak City - Nurul Paujiah; Sukardi Sukardi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to find out whether there is a relationship between price and service quality. With a positive data collection strategy and a sample size of 100 participants, this research applies associative methodology. Participants must be residents of Pontianak City, aged 17–50 years. Statistical methods used in the analysis include: multiple linear regression, correlation and determination coefficients, simultaneous testing (F test), and partial testing (t test). The data are linear, normally distributed, and show no signs of multicollinearity; these findings were confirmed by standard assumption tests. These variables have a strong relationship with each other, shown by a correlation value of 0.785. Based on the coefficient of determination (R2), the variables included in this study contributed 62% to purchasing decisions, while the remaining 38% was influenced by other factors that could not be explained. Initial research shows that price has no significant effect on purchasing decisions. On the other hand, service quality has a significant influence on purchasing decisions.